Perlindungan Hukum Bagi Korban Penyebaran Data Pribadi Oleh Penyedia Jasa Pinjaman Online Illegal dalam Perspektif Viktimologi - Muhammad Subhan; Nur Muttaqi, Nabila Ihza (Delicti : Jurnal Hukum Pidana Dan Kriminologi, 2024)
This research aims to analyze problems related to legal protection for victims of the distribution of personal data by illegal online loan service providers from a victimology perspective. Victims of the distribution of personal data by online loan service providers have not had their rights fully guaranteed because there are no comprehensive regulations governing it. As normative legal research, this research uses a statutory approach and a conceptual approach. Therefore, conducting the study is only limited to statutory regulations related to the object to be studied and legal literature. The legal materials that were collected were then compiled descriptively for qualitative analysis. The research results concluded that the victim as the injured party can apply for compensation as regulated in Article 26 paragraphs (1) and (2) of the ITE Law. Legal protection for victims of the distribution of personal data carried out by online loan service providers is that the state has not provided guarantees of protection to service users because regulations regarding personal data are still sectoral so they are not yet effective and are still spread across several settings, this means that the protection of personal data is not optimal at all person to ensure the basic right for citizens to live safely